1986
DOI: 10.1007/bf00500085
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of tyrosine hydroxylase from PC-12 cells by catechol derivatives

Abstract: Several drugs with a catechol moiety were studied for their potency to inhibit tyrosine hydroxylase (TH) from PC-12 cells in vitro. When the natural compounds tested were compared, dopamine, norepinephrine and 2(3,4-dihydroxyphenyl)-ethanol (DOPET) were most effective (IC50 between 1.4 and 3.6 microM with 0.5 microM 6(R,S)-L-erythro-5,6,7,8-tetrahydrobiopterin as cofactor). 3,4-Dihydroxyphenylalanine (DOPA; IC50: 35 microM) and 3,4-dihydroxyphenylacetic acid (DOPAC; IC50: 180 microM were less potent inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…Nevertheless, as has already been stated, in the present study the reductions in in vivo tyrosine hydroxylase activity determined after acute treatment with clorgyline were still maintained after the 14-day treatment with this drug. This persistent reduction could be a consequence of the inhibition of the synthesis provoked by increased levels of the end product of the biosynthetic route [42] or due to a reduction in the expression of tyrosine hydroxylase in the rat brain, as has been found after chronic treatment with tricyclic antidepressants, MAO inhibitors, and selective inhibitors of the serotonin uptake [43][44][45]. Thus, it has been suggested that the change in the expression of tyrosine hydroxylase could be a common mechanism of adaptation after chronic treatment with drugs which increase neurotransmitter availability [43].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as has already been stated, in the present study the reductions in in vivo tyrosine hydroxylase activity determined after acute treatment with clorgyline were still maintained after the 14-day treatment with this drug. This persistent reduction could be a consequence of the inhibition of the synthesis provoked by increased levels of the end product of the biosynthetic route [42] or due to a reduction in the expression of tyrosine hydroxylase in the rat brain, as has been found after chronic treatment with tricyclic antidepressants, MAO inhibitors, and selective inhibitors of the serotonin uptake [43][44][45]. Thus, it has been suggested that the change in the expression of tyrosine hydroxylase could be a common mechanism of adaptation after chronic treatment with drugs which increase neurotransmitter availability [43].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular DA content is mainly within vesicles (Mosharov et al, 2006), and since norepinephrine (NE) is produced exclusively within vesicles by the action of DA-b-hydroxylase acting on DA taken up from the cytoplasm, enhanced vesicular uptake would be expected to increase cell contents of endogenous DA and NE. MAO inhibition may also act indirectly to decrease DA synthesis via enhanced feedback inhibition exerted by accumulation of DA in the cytoplasm (Ames et al, 1978;Laschinski et al, 1986;Gordon et al, 2008). Since DOPA is the immediate product of enzymatic hydroxylation of tyrosine, decreased tyrosine hydroxylase activity would be expected to attenuate DOPA production (Goldstein et al, 1987;Kvetnansky et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the ability of DOPAL to covalently modify Lys residues via the aldehyde (Rees et al 2009), forming a Schiff-base structure predicted to interfere with normal protein function. Currently, specific protein targets of DOPAL are unknown, but previous studies have revealed that catechols and other DA-metabolism products interact with and inhibit tyrosine hydroxylase (TH), the rate-limiting step in DA synthesis (Laschinski et al 1986, Xu et al 1998). …”
Section: Introductionmentioning
confidence: 99%